IMMU-05. IMMUNE STIMULATION AND IMMUNE CHECKPOINT INHIBITION PROVIDED BY A SINGLE AGENT: AN ONCOLYTIC HSV EXPRESSING A scFv ANTIBODY AGAINST PD-1 - Passaro, Carmela (Neuro Oncol, 2017)
Glioblastoma multiforme (GBM), a deadly brain tumor, is resistant to current standard of care treatments including surgery and chemo-radiotherapy. This cancer is also characterized by a highly immunosuppressive microenvironment. Immune checkpoints inhibitors (such as the antiPD-1 antibody) efficiently restore T-cell activity and have been recently approved by the FDA for the treatment of several cancers. I hypothesize that an oncolytic HSV (oHSV), a self-replicating biologic agent for tumor, can disrupt the immunosuppressive GBM microenvironment and stimulate anti-tumor T cell immunity. Further, combining this with PD-1 blockade locally in the tumor maximizes antitumor immune effects. To test this hypothesis in immunocompetent mice models, I developed a new oHSV that expresses a single-chain variable fragment (scFv) antibody against mouse PD-1 to block the PD-L1:PD-1 axis signaling pathway. Preliminary experiments demonstrate that this new oHSV1 expressed and secreted the scFv antibody in several mouse glioma cell lines retaining the same cytotoxic activity of the parental virus. Moreover, the secreted scFv antibody were efficiently able to bind to the mouse PD-1. An in vivo orthotopic glioma mouse model resulted in a significant improvement of median survival time with oHSVscFvPD-1 compared to untreated mice (69 vs 22 days). Long-term survivors mice have been also re-challenged with the same mouse glioma cell line in the contralateral hemisphere showing a memory response against the tumor. Overall, the results obtained by my experiments could then justify testing the new oHSVscFvPD-1 virus in a phase I human clinical trial and/or lead to additional approach for the treatment of human glioblastoma.